PERANCANGAN LOGO DAN MEDIA PROMOSI PARIWISATA ISLAMI DI PULAU PENYENGAT MENGGUNAKAN TEKNIK FOTOGRAFI LANDSCAPE SEBAGAI UPAYA MENINGKATKAN BRAND AWARENESS - Yudhi Martha Nugraha; Nor Azlin Binti Hamidon (Prosiding Seminar Nasional Pakar, 2018)
The purpose of designing the logo and promotional media penyengat island is to make a islamic tourist attraction in kepri (riau archipelago). The research was conducted with qualitative methods of doing interviews, documentation, observation and literature study to get the data used to support the manufacture of logo design concepts and media promotion. The concept in this study was obtained from the SWOT analysis, STP, and USP then the adjective derived dikerucutkan back so "cozy" was elected to the keywords in this study. In the Oxford dictionary of English "cozy" has the meaning that is interesting and fun. In such case, this concept seems to be pleasant to have a close relationship with travel penyengat island. So in this design to be visualized creatively with the object that looks nice is mosque, and "traditional transport" which can be around in travel penyengat island. Results of designing the logo and media campaign is to make the penyengat island as a major Islamic tourist destination in kepri (riau archipelago).